Peran Kalyāṇamitta dan Strategi Mengatasi Tantangan Sikap Hormat Siswa di Era Teknologi Modern - Dysan Amaliana; Mujiyanto (STAB Kertarajasa, 2025)
The aim of this study is to examine the role of Kalyāṇamitta as a moral guide in guiding students to develop a respectful attitude in the era of modern technology. The literature review method is used as the main approach, accessing relevant literature from various sources. The research findings indicate that Kalyāṇamitta plays a significant role in shaping students' attitudes, especially in emotional management and personal growth. The impact of technology on student attitudes is complex, involving social interaction, the development of attitudes toward the environment, and influence on attitudes toward teachers. To address these challenges, the development of a Digital Ethics Education Program and the integration of character values into the curriculum are proposed. Strengthening the role of teachers, parental involvement, the development of interactive educational applications, digital content supervision, and collaboration with digital ethics experts are also considered crucial steps. Overall, a wise and planned approach is necessary to minimize negative impacts and maximize the positive potential of technology in shaping student attitudes in the modern era.